PERKAWINAN CAMPURAN DI INDONESIA: Antara Kebutuhan atau Gaya Hidup - Suud Sarim Karimullah; Arif Sugitanata; Regita Amelia Cahyani (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2022)
The purpose of writing this article is to discuss mixed marriages that occur in Indonesia because the practice of mixed marriages is something that cannot be denied, both interfaith marriages and nationalities. Then, using a library study through data collection in its preparation using various journals and books that still have relevance to the object of discussion in the preparation of this article is the type of study that will be used. Furthermore, the data used in this study is a qualitative approach with a descriptive-analytic nature of research. The results of this study state that mixed marriages are a necessity if both partners have the same harmony and commitment in building the ark of domestic life. Then, mixed marriage is also a lifestyle if both partners want a different partner from the surrounding community which is the main attraction, or even a need to fulfil a lifestyle for the perpetrators.